The Belt and Road initiative in Italy: Five case studies - Beatrice Gallelli; Francesca Ghiretti (Peter Lang International Academic Publishers, 2023)
Italy's officially joining the China-led Belt and Road Initiative sparked a fierce debate. By analysing five fields of cooperation, the volume sheds light on whether the bilateral agreement has brought about an intensification of bilateral collaboration as wished by the Italian government at the time and whether the concerns around it have materialised. The contributions will show that potential risks coexist alongside unsubstantiated ones.
Keywords: 330; Beatrice; Belt; Bilateral agreement between Italy and China; Bilateral collaboration; case; China-led Belt and Road Initiative; Francesca; Gallelli; Ghiretti; initiative; Italy; Kamel; Lorenzo; Road; studies